Reinterpretation of Gender-Biased Hadiths: A Contextual Approach Towards Gender Equality in Islam - Fauziah, Mira (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2024)
Studies on the hadiths of Prophet Muhammad (PBUH) often perceived as gender-biased are frequently conducted through textual approaches, which can result in interpretations that are unfair to women. This approach contradicts the values of gender equality enshrined in the Qur'an. Therefore, contextual analysis is necessary to understand these hadiths in a manner that is more relevant to the dynamics of modern society. This study employs a descriptive-analytical approach using qualitative methods. Primary data, including hadith collections such as Sahih al-Bukhari and Sahih Muslim, as well as Qur'anic exegeses such as Tafsir Ibn Kathir, are analyzed using historical, linguistic, and sociocultural approaches. Modern literature, including the works of Nasaruddin Umar and Muhammad Syahrur, is used as secondary references to support the analysis. The study finds that hadiths such as